2021
DOI: 10.1002/cam4.4046
|View full text |Cite
|
Sign up to set email alerts
|

Global, regional and national incidence, mortality and disability‐adjusted life‐years of skin cancers and trend analysis from 1990 to 2019: An analysis of the Global Burden of Disease Study 2019

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 35 publications
(64 reference statements)
0
62
0
Order By: Relevance
“…Deficiencies in zinc and folic acid also affect the occurrence of alopecia areata ( 16 ). The increases in the incidence and DALYs in Western Sub-Saharan Africa and South Asia might be due to the increase in population growth, urbanization, increased household income, increased self-examination, and screening programs, improved access to early detection ( 17 ). Besides, in Asian societies, hair often represents an important factor in femininity, fertility, and female attractiveness, and thus may lead to higher disease awareness.…”
Section: Discussionmentioning
confidence: 99%
“…Deficiencies in zinc and folic acid also affect the occurrence of alopecia areata ( 16 ). The increases in the incidence and DALYs in Western Sub-Saharan Africa and South Asia might be due to the increase in population growth, urbanization, increased household income, increased self-examination, and screening programs, improved access to early detection ( 17 ). Besides, in Asian societies, hair often represents an important factor in femininity, fertility, and female attractiveness, and thus may lead to higher disease awareness.…”
Section: Discussionmentioning
confidence: 99%
“…burden, although evidence of declining melanoma incidence in younger age groups in some populations continues to emerge An analysis of Global Burden of Disease data found that in 2019, there were an estimated 4.0 million basal cell carcinomas (BCCs), 2.4 million cutaneous squamous cell carcinomas (SCCs), and 0.3 million malignant melanomas globally [203]. There were ~ 63,000 deaths due to melanoma and 56,000 due to SCC (and none due to BCC).…”
Section: Skin Cancer Continues To Exert a Considerablementioning
confidence: 99%
“…CM is an increasingly concerning public health issue, mainly due to its rising incidence, fast metastasis and high mortality rates ( 1 ). CM arises from the malignant transformation of melanocytes found in the skin epidermis, which produce the photoprotective pigment melanin and are also involved in ROS/RNS scavenging, thermoregulation and immunomodulation ( 2 4 ).…”
Section: Introductionmentioning
confidence: 99%